THE MITIGATION OF SCIENTIFIC CLAIMS IN RESEARCH PAPERS: A COMPARATIVE STUDY - Martín Martín, Pedro (International Journal of English Studies, 2008)
In the context of academic writing, authors tend to mitigate the force of their scientific claims by means of hedging devices in order to reduce the risk of opposition and minimise the face threatening acts that are involved in the making of claims. This study explores the phenomenon of hedging in the research article (RA) from a cross-cultural perspective. To this end, a total of 40 RAs written in English and Spanish in the field of Clinical and Health Psychology were analysed in terms of the frequency of occurrence and distribution of the various strategies and the linguistic devices associated to each strategy which perform a hedging function in the different structural units of the articles. The results of the comparative quantitative analyses revealed that there are similarities between the two languages regarding the distribution of hedges across the structural units of the RAs, although a certain degree of rhetorical variation was also found mainly in terms of the frequency of use of the strategy of indetermination (i.e. modality devices and approximators) which occurs to a much greater extent in the English texts. This suggests that the English RAs in the field of Clinical and Health Psychology, as a whole, involve more protection to the author’s face.